2022
DOI: 10.1016/j.diabres.2021.109155
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic foot ulcer disease in African continent: ‘From clinical care to implementation’ – Review of diabetic foot in last 60 years – 1960 to 2020

Abstract: The prevalence of diabetes mellitus is increasing globally and the greatest potential increases in diabetes will occur in Africa. Data suggest that these increases is associated with rapid demographic, sociocultural and economic transitions. There will be a parallel increase in the complications of diabetes and among the various complications those related to diabetic foot disease are associated with the highest morbidity and mortality.Diabetic Peripheral neuropathy (DPN) is the most common cause of diabetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 131 publications
2
20
0
Order By: Relevance
“…Many patients treated corns, calluses and wounds on their own. This is consistent with the findings of studies conducted around the world ( 34 36 ). Patients chose to self-treat their foot problems, possibly due to a lack of foot-care knowledge or poor availability of medical facilities in rural areas.…”
Section: Discussionsupporting
confidence: 93%
“…Many patients treated corns, calluses and wounds on their own. This is consistent with the findings of studies conducted around the world ( 34 36 ). Patients chose to self-treat their foot problems, possibly due to a lack of foot-care knowledge or poor availability of medical facilities in rural areas.…”
Section: Discussionsupporting
confidence: 93%
“…1 Data has suggested that this increase is connected to rapid demographic, sociocultural and economic transitions. 3 …”
Section: Introductionmentioning
confidence: 99%
“…1 Data has suggested that this increase is connected to rapid demographic, sociocultural and economic transitions. 3 With an increase in diabetes comes a rise in micro-and macrovascular complications, which could negatively impact the health of diabetic patients. This together with neuropathy leads to further complications and an increase in the incidence of lower limb amputations due to non-healing diabetic foot ulcers (DFUs).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic foot ulcers are a common complication in diabetics. Diabetic foot ulcers can cause substantial disability, which can reduce life expectancy (Abbas and Boulton, 2022). Research result of Almobarak et al (2017) showed that the prevalence of diabetic foot ulcers in type 2 Diabetes Mellitus was 18.1%.…”
Section: Introductionmentioning
confidence: 99%